Forecasting the Tourism Demand of North Cyprus - Bıçak, Hasan Ali; Altınay, Mehmet; Jenkins, Hatice (Journal of Hospitality & Leisure Marketing / Taylor and Francis Online, 2005)
This study analyzes the demand for tourism services in North Cyprus and makes demand projections. The findings of the regression analysis shows that there is a positive relationship between the number of tourists staying in tourist accommodations in North Cyprus and the real national income of the tourist generating country with a negative relationship between the volume of tourists from a given country and the relative prices of the two countries. The study continues with a trend analysis of tourism demand and uses the trend values in projecting annual as well as monthly tourist arrivals to North Cyprus.
Keywords: North Cyprus; Tourism Demand; Trend Analysis